2023
DOI: 10.1038/s41598-023-29017-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BAP1 with small compound inhibitor for colon cancer treatment

Abstract: BRCA1-associated protein-1 (BAP1) is a ubiquitin C-terminal hydrolase domain-containing deubiquitinase. The gene encoding BAP1 is mutated in various human cancers, including mesothelioma, uveal melanoma and renal cell carcinoma. BAP1 plays roles in many cancer-related cellular functions, including cell proliferation, cell death, and nuclear processes crucial for genome stability, such as DNA repair and replication. While these findings suggest that BAP1 functions as a tumor suppressor, recent data also suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous studies have provided con icting evidence, and the role of BAP1 seems to be context-dependent. Regarding the role of BAP1 in CRC, only two studies have explored the association between BAP1 expression and prognosis, demonstrating con icting results [17,18] . One study demonstrated that low BAP1 expression was an independent factor for poor prognosis in patients with CRC [18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have provided con icting evidence, and the role of BAP1 seems to be context-dependent. Regarding the role of BAP1 in CRC, only two studies have explored the association between BAP1 expression and prognosis, demonstrating con icting results [17,18] . One study demonstrated that low BAP1 expression was an independent factor for poor prognosis in patients with CRC [18] .…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that low BAP1 expression was an independent factor for poor prognosis in patients with CRC [18] . However, another study demonstrated that elevated BAP1 expression was observed in colon cancer and was signi cantly associated with poor prognosis, probably through the regulation of cell proliferation, apoptosis, and DNA replication [17] . In the present study, BAP1 expression was rarely observed in normal gland cells of the colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation